Web-Based Goods Ordering Information System Case Study on CV. Tytus Furniture Semarang - Aditama Surya Permana; Eri Yanto; Evanti Andriani (International Forum of Researchers and Lecturers, 2025)
The development of the business world relies on technology information Already become absolute thing.​ His height activity data transactions and exchange information in online communication media and the internet is one technology For overcome activity everyday life in the era of globalization moment This. CV. TYTUS FURNITURE SEMARANG is A moving company​ in field Furniture sales , such as : table chair room visitor . Problem sale CV products. TYTUS FURNITURE SEMARANG is limitations consumer in obtain information product , type product , price product , because consumer must come direct to company or waiting for sales to come give information about company , so No can save time and costs , turnover sale not enough in accordance hope , not yet exists processing sales and consumer data reports in a way fast and efficient. For that's system very online sales required moment This For develop something company , because system the present For give real solution​ Where system the online sales can fulfil need will transaction business online with​ easy and fast with using a MySQL database with Language PHP programming . System information This capable give information product to consumer online , and can give information products sold​​​ to consumer . Based on background behind problem above , then writer take title